Virtuosité technique et esthétique artisanale dans l’architecture aux xviie et xviiie siècles - Valérie Nègre (Images Re-Vues)
Based on the study of texts produced by French architectural theoreticians and master craftsmen, this article examine how technical virtuosity was viewed in architecture in the seventeenth and eighteenth centuries. Theorists' discourses show that while some forms of technical virtuosity reflected artists' ingenuity, others were regarded as characteristics of trades. Having established which skills were likely to downgrade architects, the discussion focuses on two types of virtuosity: feint and thoroughness. The article argues the existence of an "artisanal aesthetic", i.e. craftsmen’ intentional search for shapes and performances that produce effects. conservation, restoration, documentation, art handling, storage, complex artworks, ethnography, ethnomethodology